Peculiarities of Isolated Clusters Operation - Anastasiya A. Sozinova; Sergey V. Novikov; Sergey N. Kosnikov; Galina I. Nemchenko; Elena E. Alenina (International Journal of Economics and Financial Issues, 2016)
Many countries with their policy of dynamic development and considered active course of support for commercial activities focused on achievement of socio - economic growth, conduct the process of mobile diversified interaction of various enterprise-wide, branches of many sectors, spheres and levels step-by-step. Many countries of the empyrean with different levels of economic processes have revealed the common pattern that is shown in the most positive formation of diversified unions of enterprises which are grouped round large companies of leaders on the basis of production and technological, scientific, technical and commercial ties within territories geographically limited. One of the main tasks of the paper is consider the conceptual framework of isolated clusters with innovative policy of development. Its main directions of development of isolated systems are specified. The paper also develops the direction of increased efficiency of intellectual human resource application in the innovative process. The purpose of the paper is to analyze the key effective forms of work of innovative isolated clusters of the isolated territory, their impact on modern economic state development, human resource application and value in certain areas of activities.